The effectiveness of primary care based risk stratification for targeted latent tuberculosis infection screening in recent immigrants to the UK: a retrospective cohort study. Issue 4 (19th November 2013) - Panchal, Rakesh K; Browne, Ivan; Monk, Philip; Woltmann, Gerrit; Haldar, Pranabashis
Abstract : Background: Most UK tuberculosis (TB) cases occur in immigrants from high TB incidence areas, implicating reactivation of imported latent TB infection (LTBI). Strategies to identify and treat immigrant LTBI in primary care at the time of first registration (coded Flag-4) may be effective. Methods: This was an 11-year retrospective cohort study to evaluate effectiveness of LTBI screening in recent immigrants to Leicestershire at their time of primary care registration. We examined the temporal relationship between dates of Flag-4 primary care registration (n=59 007) and foreign-born TB (FB-TB) cases (n=857), for immigrants arriving to the UK after 1999. TB diagnosed >6 months after registration was considered potentially preventable with screening. Primary outcomes were the potentially preventable proportion of FB-TB and the number needed to screen (NNS) of immigrants to identify one potentially preventable case, stratified by age and region of origin. Results: 250 cases (29%) were potentially preventable in Flag-4-registered immigrants. Overall, 511 cases (60%) were potentially preventable among primary-care registered immigrants, implying a significant proportion without Flag-4 status. Prospective TB incidence (95% CI) after Flag-4 registration was 183 (163 to 205) cases/100 000 person-years, with a NNS (95% CI) of 145 (130 to 162). Targeted screening was most effective for 16–35 year olds from TB incidence regions 150–499/100 000 (NNS (95% CI)=65 (57 to 74), preventing 159 (18.7%) cases). Unpreventable TB risk increased with delayed primary care registration after UK entry (p<0.001) and was associated with HIV seropositivity (relative risk (95% CI)=1.89 (1.25 to 2.84), p=0.003). Conclusions: LTBI screening at primary care registration offers an effective strategy for potentially identifying immigrants at high risk of developing TB.